Assessing Emotional Intelligence in Leaders and Organisations: Reliability and Validity of the Emotional Capital Report (ECR). (18th August 2015) - Newman, Martyn; Purse, Judith; Smith, Ken; Broderick, John
Abstract : This study examined the reliability and validity over a 5-year period of a new measure of emotional intelligence (EI), the Emotional Capital Report (Newman & Purse, 2007 ), in a sample of 6, 874 professional people from 11 different geographical regions. Results indicated that the ECR had adequate factor structure and the component scales had good internal consistency and test–retest reliability. Age and gender analyses revealed minor differences between males and females on seven ECR scales and significant age-related differences across all scales. The ECR scales had a meaningful pattern of convergent validities in relation to measures of normal personality, depression, and psychopathology. Construct validity revealed that although measuring similar constructs to personality and another well-known general measure of EI, the ECR was measuring something distinctive that pertains to the experience of people in professional roles. Furthermore, high scores on the ECR correlated with jobs involving high emotional labour requirements. Results indicated that these groups scored consistently higher on all ECR scales. It is recommended future research develop strategies for further validation of the ECR, as well as the construct of EI.